RISING TEACHER COMPETENCE THROUGH LESSON STUDY IN INTEGRATED SCIENCE EDUCATION WITH JELAJAH ALAM SEKITAR APPROACH - Susilowati, Sri Mulyani Endang; Rusilowati, Ani (IJRDO- Journal of Educational Research, 2017)
Sciences teachers in Junior High School are generally Physics and Biology Education graduates. Whereas, 2013 curriculum provides Biology and Physics as an integrated subject, natural sciences. Hence, Physics Education graduates teachers have trouble in teaching Biology and vice versa. The purpose of this study is to improve the professionalism of the science teacher through the lesson study (LS). This research is an action research conducted in collaboration with the junior high school science teachers and post-graduate students of Science Education and Elementary Education program, Universitas Negeri Semarang. LS determined several topics which will be developed as a sciences learning kit for seventh graders of Senior High School. Implementation of the learning kit was also implemented by LS. The results showed that LS could improve the teachers’ professionalism that includes the ability of teachers to prepare learning kit, implementing in the classroom using some innovative learning models and assessing the students. It is suggested that LS activities need to be developed and implemented consistently because it is effectively proven to improve the ability of teachers.